Disconnected Gas Transport in Steady‐State Three‐Phase Flow. Issue 12 (9th December 2021) - Alhosani, Abdulla; Selem, Ahmed M.; Lin, Qingyang; Bijeljic, Branko; Blunt, Martin J.
Abstract: We use high‐resolution three‐dimensional X‐ray microtomography to investigate fluid displacement during steady‐state three‐phase flow in a cm‐sized water‐wet sandstone rock sample. The pressure differential across the sample is measured which enables the determination of relative permeability; capillary pressure is also estimated from the interfacial curvature. Though the measured relative permeabilities are consistent, to within experimental uncertainty, with values obtained without imaging on larger samples, we discover a unique flow dynamics. The most non‐wetting phase (gas) is disconnected across the system: gas flows by periodically opening critical flow pathways in intermediate‐sized pores. While this phenomenon has been observed in two‐phase flow, here it is significant at low flow rates, where capillary forces dominate at the pore‐scale. Gas movement proceeds in a series of double and multiple displacement events. Implications for the design of three‐phase flow processes and current empirical models are discussed: the traditional conceptualization of three‐phase dynamics based on analogies to two‐phase flow vastly over‐estimates the connectivity and flow potential of the gas phase. Key Points: Gas flow is disconnected at steady‐state conditions, explaining the low gas relative permeability seen in this water‐wet three‐phase system Intermittent gas‐oil flow is observed in intermediate‐sized pores despite flowing at low flowrates, where capillary forces are dominant The traditional use of two‐phase data to predict three‐phase flow vastly over‐estimates the connectivity and mobility of the gas phase